2019
DOI: 10.1590/0366-69132019653732385
|View full text |Cite
|
Sign up to set email alerts
|

Cinza de biomassa rica em calcário como material carbonático em sistemas cimentícios de base Portland

Abstract: Resumo O uso de materiais alternativos, em substituição ao clínquer, tem sido amplamente estudado, a fim de reduzir custos e minimizar os danos ambientais causados pela produção do cimento Portland. Investigou-se a influência do uso da cinza de algaroba (Prosopis juliflora), material rico em carbonato de cálcio, nos mecanismos de hidratação e formação das principais fases hidratadas do cimento Portland. As características físicas e químicas das matérias-primas foram avaliadas. Composições com 5%, 10% e 15% de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
4
0
5
Order By: Relevance
“…The size of Algaroba wood ash grains that pass through sieve no. 200 is between 2.46 μm and 43.91 μm (NASCIMENTO et al, 2019;MELO et al, 2018), which is within the grain size required to use as a filler in SCC systems. Thus, owing to the similarity of this type of ash with the natural limestone filler regarding its chemical composition and possible treatments in the physical aspect, it is observed that SCC can incorporate calcium-rich ashes as an alternative filler to ensure its fluidity.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…The size of Algaroba wood ash grains that pass through sieve no. 200 is between 2.46 μm and 43.91 μm (NASCIMENTO et al, 2019;MELO et al, 2018), which is within the grain size required to use as a filler in SCC systems. Thus, owing to the similarity of this type of ash with the natural limestone filler regarding its chemical composition and possible treatments in the physical aspect, it is observed that SCC can incorporate calcium-rich ashes as an alternative filler to ensure its fluidity.…”
Section: Introductionmentioning
confidence: 76%
“…Likewise, no losses were observed in the SCC compression strengths for TFC (100% of limestone filler), and TFCFA (50% of limestone filler + 50% of calcium-rich ash filler) and their respective corrections when exposed to heat during the mixing process. Nascimento et al (2019) also reported the precipitation of hemicarboaluminate and monocarboaluminate phases in calcium-rich systems using Albaroba ashes.…”
Section: Compressive Strengthmentioning
confidence: 95%
See 1 more Smart Citation
“…The calcium and silicon oxides were the major constituents in the studied samples and together were responsible for the hydration reactions of silicates, corresponding to more than 60% of volume in the cement reactions [6]. The variation of the calcium and silicon elements in the cement directly interferes in the C 3 S and C 2 S anhydrous phases, in which a higher concentration of calcium leads to a preponderant production of alite, and is the main element responsible for the hydrated C-S-H and Ca(OH) 2 phases [30,31]. The aluminum and iron oxides are no less important, being responsible for aluminate reactions and corresponding to 20% of the volume of the reactions which occur in the cement.…”
Section: Resultsmentioning
confidence: 99%
“…Segundo Nascimento et al, (2019), o uso do filler calcário alternativo como substituto parcial do clínquer, na produção do cimento, reduz o consumo energético e a emissão de dióxido de carbono (CO2), além de reduzir a exploração de calcário e argila, que são as matérias-primas do clínquer.…”
Section: Introductionunclassified